P-167 Male infertility and polycystic ovary syndrome (PCOS) affect absolute and relative embryo morphokinetics observed by time-lapse imaging. (30th June 2022) - Garçon, V; Dietrich, J.E; Strowitzki, T; Freis, A
Abstract: Study question: This study aimed to test if morphokinetics are altered in embryos from patients with male infertility, polycystic ovary syndrome (PCOS) or recurrent pregnancy loss (RPL). Summary answer: Morphokinetics differed significantly between embryos from patients with male infertility or PCOS compared to the control groups, possibly suggesting a negative impact on development potential. What is known already: Time-lapse imaging technology allows continuous observation of embryonic morphology and developmental kinetics during the preimplantation period. The ESHRE Working group on Time-lapse technology recently summarised common absolute morphokinetic time points and intervals [DOI: 10.1093/hropen/hoaa008]. Additionally, four relative morphokinetic expressions were introduced by Cetinkaya et al.: Cleavage Synchronicity 2-8-, 4-8-, 2-4-cell stage (CS2-8, CS4-8, CS2-4) and DNA Replication time ratio (DR) [DOI: 10.1007/s10815-014-0341-x]. A study by Freis et al. observed worse CS2-8 and CS4-8 ratios in embryos from patients with endometriosis [DOI: 10.1177/1933719117741373]. Other studies have found that male infertility and PCOS may affect morphokinetic time points. Study design, size, duration: In this retrospective observational study n = 1433 two-pronuclei oocytes from n = 433 patients between 18 and 45 years undergoing IVF/ICSI-treatment between 09/2016 and 12/2019 were examined. The use of a time-lapse incubator was obligatory. Exclusion criteria were the presence of endometriosis, history of chemotherapy, preimplantation genetic testing (PGT) cycles and genetic abnormalities. Every patient was included only once. Control groups were uterine, tubal factor and idiopathic infertility. Participants/materials, setting, methods: Male infertility (n = 928 oocytes; 288 patients) versus control (n = 400; 115), PCOS (n = 48; 14) versus control (n = 400; 115) and RPL (n = 79; 21) versus control (n = 321; 94) were compared. Patient and treatment characteristics were compared using Mann-Whitney-U and Fisher's exact test. Times normalised to fading of pronuclei (tPNf), intervals and ratios were analysed using a Generalised Linear Mixed Model (GLMM). Main results and the role of chance: The male infertility group was significantly different (p < 0.05) from the control group regarding male age (p = 0.009), fertilisation rate (p = 0.008), number of embryos per patient (p = 0.033), treatment method (p < 0.001) and use of Calcium-Ionophore (p = 0.049) or SpermMobile (p = 0.003). DR was significantly higher in the male infertility group compared to the control group (p = 0.031). The start of blastulation (tSB-tPNf; p = 0.008) and start of expansion of the blastocyst (tEB-tPNf; p = 0.002) were significantly delayed. The PCOS group was significantly different concerning female age (p = 0.023) and AMH blood level (p < 0.001). CS2-8 was significantly lower (p = 0.003) and CS2-4 significantly higher (p = 0.001) in the PCOS group compared to the control group. The time intervals from three- to four-cell (s2; p = 0.013), from five- to eight-cell (s3; p = 0.032) and from four- to eight-cell stage (ECC3; p = 0.043) were significantly longer in the PCOS group. There was no significant difference in patient or treatment related characteristics between the RPL group and the control group. Also, none of the morphokinetic parameters analysed in this study was significantly different between the groups. Limitations, reasons for caution: Small group sizes decreased further at later developmental time points. In general, time-lapse data show a high intra- and inter-observer variability. A GLMM was performed to take statistical dependencies between embryos of one patient into account. Its Gaussian assumption was partially violated by the true distribution of the data. Wider implications of the findings: These data support the hypothesis that patients' co-morbidities may affect embryo morphokinetics. The impact on clinical outcome should be examined further. Accordingly, our working group conducted another study about the predictive value of morphokinetics on blastocyst quality and implantation (DRKS-ID: DRKS00022983). The long-term goal is to improve embryo assessment. Trial registration number: not applicable